PENGARUH LIKUIDITAS, PROFITABILITAS, DAN LEVERAGE, TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR (STUDI PADA SEKTOR INDUSTRI BARANG KONSUMSI) YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2016-2020 - Novais Richa; Efni Yulia; Rahmayanti Elvi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Liquidity, Profitability, and Leverage on Financial Distress in Manufacturing companies (Studies in the Consumer Goods Industry Sector) listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The population in this study amounted to 59 companies. While the number of research samples amounted to 25 companies. The data analysis used was multiple linear regression analysis with the help of SPSS 24.0. The results of the research show (1) liquidity has no effect on financial distress; (2) Profitability has a negative effect on financial distress; (3) Leverage has a positive effect on financial distress; and (4) Liquidity, profitability, and leverage simultaneously have a significant effect on financial distress.Keyword: Liquidity, Profitability, Leverage, Financial Distress